Soy isoflavone genistein upregulates epithelial adhesion molecule E-cadherin expression and attenuates -catenin signaling in mammary epithelial cells - Ying Su; Frank A. Simmen (2008)
Breast cancer risk is highly modifiable by diet; however, mechanisms underlying dietary protection against mammary tumorigenesis remain poorly understood. A proportion of breast carcinomas is associated with deregulation of β-catenin stability and amplification of c-Myc expression. We recently showed that dietary exposure to the soy isoflavone genistein (Gen) inhibited Wnt transduction in rat mammary epithelial cells in vivo . Here, we explored the role of Gen on cell adhesion protein, E-cadherin, expression to downregulate β-catenin proto-oncogene function. In mammary glands of female rats exposed to dietary Gen, E-cadherin and β-catenin protein levels were increased, concurrent with higher β-casein gene expression. In HC11 mouse mammary epithelial cells, Gen diminished basal and Wnt-1-induced cell proliferation and attenuated Wnt-1 targets c-Myc and Cyclin D1 expression. Whereas, Gen had no effect on E-cadherin transcript levels, the abundance of membrane E-cadherin protein and of E-cadherin–β-catenin adhesion complex was increased by Gen, attendant with downregulation of Wnt-1-induced free β-catenin accumulation in cytosol. Gen inhibition of Wnt-induced c-Myc expression was mimicked by an estrogen receptor (ER)-β-specific but not ER-α-specific agonist and was attenuated with loss of ER-β expression, concordant with decreased E-cadherin expression. E-cadherin small-interfering RNA targeting eliminated Gen inhibition of Wnt-stimulated c-Myc expression and promoted Gen induction of basal c-Myc transcript levels and subsequent proliferation. Our studies identify E-cadherin as a Gen cellular target and demonstrate that the dichotomy in mammary epithelial response to Gen may be a function of cellular E-cadherin expression.